Adenoid cystic carcinoma of the breast with cerebral metastisation: a clinical novelty. (7th October 2011) - Silva, Ines; Tome, Vera; Oliveira, Joao
Abstract : Adenoid cystic carcinoma (ACC) is a rare variant of adenocarcinoma of the breast. It affects mainly minor and major salivary glands, but may also occur in many others locations such as: breast (<1% of all breast cancers), lung, trachea, cervix and Bartholin's gland. Its prognosis is excellent, contrary to the extra-mammary form. In fact, metastisation is rare (there are only seven clinical cases with metastisation described in literature and the lung is the most affected organ) and when it occurs, generally, there is no axillary node involvement. The authors present the case of a 37-year-old patient, Caucasian, premenopausal, referred to our Cancer Institute with the diagnosis of ACC of the right breast. This case was peculiar because of its multiple and fatal metastisation pattern–nodal, pulmonary, hepatic, osseous and late multifocal cerebral involvement (brain stem and cerebellum). This is the first case-report of ACC with cerebral metastisation.